High acetylsalicylic acid dosing in infants after modified Blalock–Taussig shunt. (11th February 2019) - Saini, Arun; Joshi, Ashwini D.; Cowan, Krista M.; Wayne Gatewood, Connor; Kumar, Susheel T. K.; Allen, Jerry; Shah, Samir H.; Nouer, Simonne S.; Jones, Tamekia; Knott-Craig, Christopher J.; Boston, Umar S.
Abstract: Objective: Shunt-related adverse events are frequent in infants after modified Blalock–Taussig despite use of acetylsalicylic acid prophylaxis. A higher incidence of acetylsalicylic acid-resistance and sub-therapeutic acetylsalicylic acid levels has been reported in infants. We evaluated whether using high-dose acetylsalicylic acid can decrease shunt-related adverse events in infants after modified Blalock–Taussig. Methods: In this single-centre retrospective cohort study, we included infants ⩽1-year-old who underwent modified Blalock–Taussig placement and received acetylsalicylic acid in the ICU. We defined acetylsalicylic acid treatment groups as standard dose (⩽7 mg/kg/day) and high dose (⩾8 mg/kg/day) based on the initiating dose. Results: There were 34 infants in each group. Both groups were similar in age, gender, cardiac defect type, ICU length of stay, and time interval to second stage or definitive repair. Shunt interventions (18 versus 32%, p=0.16), shunt thrombosis (14 versus 17%, p=0.74), and mortality (9 versus 12%, p=0.65) were not significantly different between groups. On multiple logistic regression analysis, single-ventricle morphology (odds ratio 5.2, 95% confidence interval of 1.2–23, p=0.03) and post-operative red blood cells transfusion ⩾24 hours [odds ratio 15, confidence interval of (3–71), p<0.01] were associated with shunt-related adverse events. High-dose acetylsalicylic acid treatment [odds ratio 2.6, confidence interval of (0.7–10), p=0.16] was not associated with decrease in these events. Conclusions: High-dose acetylsalicylic acid may not be sufficient in reducing shunt-related adverse events in infants after modified Blalock–Taussig. Post-operative red blood cells transfusion may be a modifiable risk factor for these events. A randomised trial is needed to determine appropriate acetylsalicylic acid dosing in infants with modified Blalock–Taussig.